Analisis Potensi Bahaya dan Penilaian Risiko K3 dengan Metode Hazard and Operability (HAZOP) - ratih rahma (Universitas Widya Gama Mahakam Samarinda, 2020)
Gamelan Industry Center of Ponorogo Regency has a variety of potential hazards (low to extreme categories) from the production process. However, the level of workers aware of the importance of occupational safety and health is still low. The purpose of this research is to analyze the potential for hazards and assess risk with the Hazard and Operability (HAZOP) method in the Gamelan Industry Center. This research is an observational descriptive study. The research object examined was the hazards and risks of occupational safety and health in the Gamelan Industry Center. The stages in the research are the identification of potential hazards and risk assessment using the HAZOP method. The results of the analysis show that there are 10 types of potential hazards and 17 kinds of risks in the Gamelan Industry Center, namely 12 extreme risks, 14 high risks, 32 moderate risks, 8 low risks. The most dominant potential hazards are noise, with an average noise intensity of 99.85 dB so that it can cause hearing loss in workers. Proposed improvement in the form of administrative improvements includes the provision of PPE that is by workers' needs, applying 5R to industry, making SOP for the use of tools and materials.